1986
DOI: 10.1079/pns19860053
|View full text |Cite
|
Sign up to set email alerts
|

The biological basis of Maintenance and its relevance to assessing Responses to nutrients

Abstract: Animals exhibit a first priority, or threshold, energy requirement that must be met from dietary intake before there will be a yield of products. When fasted, rested and held in a thermoneutral environment, animals exhibit a basal level of energy expenditure that is supported by oxidation of substrates, principally lipids and amino acids, mobilized from body tissues. It is widely presumed that the maintenance energy requirement is the dietary metabolizable energy (ME) required to meet this first-call basal met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…There may be variation between individuals as well as between breeds in the efficiency with which nutrients (food energy) are used for maintenance processes (Taylor et al 1986b). Ion transport is a major contributor to maintenance energy costs (Milligan & Summers, 1986) and has been found, in duodenal mucosa, to be enhanced in lactation in cows, although this may be as much the result of altered food consumption as a direct reflection of changed physiological state (McBride & Milligan, 1984). Genetic variations in ion transport costs have been identified as a result of selection for growth in sheep, but analogous differences in lactation have yet to be sought or identified.…”
Section: Animal Variationmentioning
confidence: 99%
“…There may be variation between individuals as well as between breeds in the efficiency with which nutrients (food energy) are used for maintenance processes (Taylor et al 1986b). Ion transport is a major contributor to maintenance energy costs (Milligan & Summers, 1986) and has been found, in duodenal mucosa, to be enhanced in lactation in cows, although this may be as much the result of altered food consumption as a direct reflection of changed physiological state (McBride & Milligan, 1984). Genetic variations in ion transport costs have been identified as a result of selection for growth in sheep, but analogous differences in lactation have yet to be sought or identified.…”
Section: Animal Variationmentioning
confidence: 99%
“…McBride 1988) and whole-body energetics (Milligan and Summers 1986). Swaminathan et al (1989) found that Na+, K+ Arpase activity accounted for 39% of wholebody 02 consumption in the guinea pig.…”
mentioning
confidence: 99%
“…The support metabolism is the increase in energetic expenses caused by the intensification of the processes of digestion, circulation, secretion, maintenance of the concentration gradients, muscular tonus and tissue renewal that occurs on levels above the energetic equilibrium (Milligan & Summers, 1986). Hence, the less the amount of metabolizable energy used for the maintenance metabolism and support metabolism, the higher the energy availability for body mass gain (energy retention in the body).…”
Section: Resultsmentioning
confidence: 99%